Clinical‐grade validation of whole genome sequencing reveals robust detection of low‐frequency variants and copy number alterations in CLL. (29th May 2018) - Klintman, Jenny; Barmpouti, Katerina; Knight, Samantha J. L.; Robbe, Pauline; Dreau, Hélène; Clifford, Ruth; Ridout, Kate; Burns, Adam; Timbs, Adele; Bruce, David; Antoniou, Pavlos; Sosinsky, Alona; et al.
Summary: The 100 000 Genome Project aims to develop a diagnostics platform by introducing whole genome sequencing (WGS) into clinical practice. Samples from patients with chronic lymphocytic leukaemia were subjected to WGS. WGS detection of single nucleotide variants and insertion/deletions were validated by targeted next generation sequencing showing high concordance (96·3%), also for detection of sub‐clonal variants and low‐frequency TP53 variants. Copy number alteration detection was verified by fluorescent in situ hybridisation and genome‐wide single nucleotide polymorphism array (concordances of 86·7% and 92·9%, respectively), confirming adequate sensitivity by WGS. Our results confirm that WGS can provide comprehensive genomic characterisation for clinical trials, drug discovery and, ultimately, precision medicine.